Characterization of sewage sludge particles influencing dewaterability - Ahmed, M Feroze; Ahmed, Tanvir (Journal of Bangladesh Academy of Sciences, 2024)
This study presents an investigation into the fundamental characteristics of sludge particles that influence the dewaterability of sewage sludge. Dewatering of sewage sludge is required for the reduction of sludge volume, sludge treatment, and safe disposal of sludges having very high pollution potentials. Particle characteristics important for dewatering, like particle size distribution, particle density, bound water content, surface charge, protein, and polysaccharide content of activated and digested sludges, were determined. Without a suitable method for analyzing the total range of particles in sewage sludge and effective density, new techniques have been developed to determine particle size distribution and particle density with reasonable accuracy. Particles larger than 45 μm were analyzed by wash sieving, while particles smaller than 45 μm were analyzed using a Coulter counter. The results from both methods were combined, maintaining their proportional contribution to the overall particle size distribution. Particle density was computed by determining the dry density and bound water content. Additionally, particle size and velocity were measured using an interference microscope, and these values were inserted into Stokes' Law equation to calculate the effective density of sludge particles. J. Bangladesh Acad. Sci. 48(2); 171-184: December 2024